Teacherpreneur Implementation Seen from the Perceptions of Vocational High School Teachers in the 21st Era - Etika Dewi Kusumaningtyas; Eka Fanti Sulistiyaningsih (Yayasan Citra Dharma Cindekia, 2022)
Teachers are professional educators with the main task of educating, teaching, guiding, directing, training, assessing, and evaluating students in early childhood education through formal education, basic education, and secondary education (UUN No. 14 2005). The basic competence of teachers in pedagogical, social, personality and professional requires development. Development in line with existing technological and scientific developments. The demand for competency development does not only come from the conditional facts of education but also from the government. The government improves and develops the competencies it has through several regulations and training contained in the Law on Teachers and Lecturers No. 14 of 2005 which explains that the government has implemented educator certification through selected tertiary institutions. Teachers as education facilitators in schools are required to develop their skills or competencies into innovative and creative works. This work which increases student motivation in learning as well as teacherpreneur abilities in teachers due to achievement is a real example of an outstanding teacherpreneur teacher is a real example of a teacherpreneur (Abdillah 2020). The teacher's initial understanding of teacherpreneur has a role in its application. Therefore, it takes an appropriate understanding of the teacherpreneur owned by the teacher.